PENGARUH AKTIVITAS PERMAINAN BOM WAKWAW TERHADAP PENINGKATAN PERKEMBANGAN MENGENAL KONSEP DAN LAMBANG BILANGAN ANAK - Putri Clawson; Repina Agnes Siagian (P3M STKIP 'Aisyiyah Riau, 2018)
This study aims to determine and analyze the Effect of Wakwaw Bomb Game Activity on Increasing Development in recognizing the Concepts and Symbols of Child Numbers in Group B of One-Roofed Kindergarten Negeri TK. This study uses a quasi-experimental method which is a study that is strived to observe problems systematically and accurately about the facts and the nature of certain objects. The sample in this study was 36 people at One Roof Kandis Kindergarten as an experimental class. Data collection techniques using observation. Based on the results of data analysis using the t test, there is an influence of wakwaw bomb game activity on the improvement of the development of knowing the concepts and symbols of child numbers in Group B of One-roofed Kindergarten TK. Because t arithmetic> t table, (11,669> 2,032 and significance <0.05 (0,000 <0.05), then Ho is rejected, so it can be concluded that there is a difference in the average time of bomb activity between pre-treatment and after treatment. From calculations with SPSS can It is also known that the average value of the Wakakaw bomb game after treatment is higher, this can be interpreted that the Wakakaw bomb game has an effect on the improvement in the development of the concepts and symbols of child numbers in Group B of One-roofed Kindergarten TK.